THE ANALYSIS OF INVOLVEMENT OF YOUNG GENERATION ON CREATIVE ECONOMIC DEVELOPMENT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2017)
This study aims to analyze the existence of young generation in the development of creative economy in Lamongan regency. This research uses descriptive quantitative design with survey research approach. The subjects of the study were self-employed entrepreneurs who tend to be economic actors in Lamongan regency with population 260,273 people and taken sample of 205 people with Purposive Sampling technique. Instrument data in the form of questionnaires, interviews and documentation. The results concluded that 19.4% of the population of Lamongan District is active as economic actors with various efforts. Based on the results of data analysis is known that 16.6% is the creative economy. While based on data from all subjects of the study, it is known that the young generation who become creative economic players as much as 9.3% of the total number of respondents. Based on the results of the research shows that there are 10 subsectors of creative economy that have been developed by the community. Overall, the involvement of the younger generation in business activities in the creative economy is still relatively small when compared with other sectors. However, when compared with fellow creative economy actors, the younger generation is more dominant. This is based on the results of data analysis showing the young generation involved in the creative economy as much as 55.9%. While the creative economic actors aged over 35 years as much as 44.1%.